COHESION AND COHERENCE IN READING ACTIVITIES OF THE 2024 INDONESIAN EFL TEXTBOOK - Nurmaya, Krisma; Hidayat, Didin Nuruddin; Husna, Nida (Jurnal Ilmiah Bina Bahasa, 2025)
Given Indonesian students’ limited exposure to English outside the classroom, textbooks play a crucial role in shaping reading development. Therefore, this study examines the cohesion and coherence of the reading texts in the Bahasa Inggris Tingkat Lanjut: Let’s Elevate Our English (Edisi Revisi 2024) textbook for the XI graders. Using Halliday and Hasan’s (1976) framework, the analysis identifies grammatical cohesive devices, reference, and conjunctions across 12 narrative, analytical exposition, and hortatory exposition texts. Coherence was analyzed through van Dijk and Kintsch’s (1983) situation model, focusing on propositional structures, local and global coherence, and genre-based superstructures. Findings reveal clear genre-dependent patterns: narrative texts rely heavily on referential cohesion to track characters and events. Meanwhile, analytical and hortatory expositions rely predominantly on explicit conjunctions to construct logical and persuasive argumentation, highlighting the pedagogical importance of genre-based cohesion for classroom instruction. Most of the texts demonstrate strong global coherence through stable macrostructures and adherence to expected genre schemata. However, the predominance of surface-level cohesive markers, particularly in expository texts, suggests limited opportunities for developing learners’ inferential and higher-order comprehension skills. Overall, the textbook provides coherent and accessible discourse models for senior high school learners. Yet, it would benefit from more varied cohesion strategies and deeper conceptual linking to support advanced academic literacy.